Iodoperchlorobenzene acts as a dual halogen-bond donor to template a [2 + 2] cycloaddition reaction within an organic co-crystal. Issue 47 (25th November 2021) - Shapiro, Nicole M.; Bosch, Eric; Unruh, Daniel K.; Krueger, Herman R.; Groeneman, Ryan H.
Abstract : The formation of three isostructural co-crystals that utilize iodoperchlorobenzene as a dual halogen-bond donor is reported. Abstract : The formation of three isostructural co-crystals that utilize iodoperchlorobenzene as a dual halogen-bond donor is reported. These molecular solids are held together by the combination of I⋯N and Cl⋯N halogen bonds to form one-dimensional polymeric chains. Curiously, these co-crystals are isostructural to a series of related solids based upon the isosteric halogen-bond donor 1, 4-diiodoperchlorobenzene. It is noteworthy that the co-crystal containing trans -1, 2-bis(4-pyridyl)ethylene undergoes a near quantitative [2 + 2] cycloaddition reaction.